Optimization of strong-base anion exchange O&M costs for hexavalent chromium treatment. (1st August 2018) - Plummer, Sarah; Gorman, Craig; Henrie, Tarrah; Shimabuku, Kyle; Thompson, Robert; Seidel, Chad
Abstract: Hexavalent chromium [Cr(VI)] in drinking water is pending regulation in California and is being considered for regulation in other locations. While strong-base anion exchange (SBA-IX) can efficiently remove Cr(VI) to low-levels that may be required to comply with future MCLs, operational and maintenance (O&M) costs can be considerable if the spent brine is disposed of as hazardous waste. Through bench- and pilot-scale experiments and full-scale demonstrations, this study examined the ability of emerging and established brine treatment and reuse techniques as well as recently developed resins to decrease O&M costs. When profiling anion elution during regeneration with nanofiltration treated and untreated spent brine, it appeared that at least 1 and 3 reuse cycles were feasible, respectively. Stannous- and ferrous-based reductants were more efficient than sulfur-based reductants when treating spent brine. Bed volumes to 8 μg/L chromium breakthrough with 7 resins varied by as much as a factor of 2 and correlated (R 2 = 0.84) with resin total exchange capacities. Spent brine reuse, segmented regeneration (an optimized brine reuse method), ferrous reduction, and nanofiltration of spent brine were estimated to decrease O&M costs by 30, 70, 63, and 61%, respectively. Selection of high performing resins was the most simple way to decrease O&M costs (up to 70% savings). The sum of nitrate and sulfate raw water equivalent concentrations was found to be the principal water quality parameter that influenced the performance of 4 resins in 7 different groundwaters because nitrate and sulfate concentrations were orders of magnitude greater than chromium concentrations. Resins with higher chromium capacities eluted more co-contaminants including arsenic, selenium, uranium, and vanadium because they likely had higher co-contaminant capacities. Co-contaminant elution was found to be complex because associations can form between regenerant and co-eluting anions. Sodium chloride was the most efficient regenerant, though other regenerants provided benefits such as enhanced uranium elution most likely by complexing with uranium to inhibit its precipitation. Nitrate peaking was found to be limited even when reusing untreated and nanofiltration treated spent brine.